2022
DOI: 10.1038/s41598-022-22271-4
|View full text |Cite
|
Sign up to set email alerts
|

Pigment signatures of algal communities and their implications for glacier surface darkening

Abstract: Blooms of pigmented algae darken the surface of glaciers and ice sheets, thereby enhancing solar energy absorption and amplifying ice and snow melt. The impacts of algal pigment and community composition on surface darkening are still poorly understood. Here, we characterise glacier ice and snow algal pigment signatures on snow and bare ice surfaces and study their role in photophysiology and energy absorption on three glaciers in Southeast Greenland. Purpurogallin and astaxanthin esters dominated the glacier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…This is, in both cases, at the height of the melt season, when liquid water (at ~0.1°C) is widespread on the glacier surface, coinciding with high bacterial and algal activity (Hamilton & Havig, 2017 ; Nicholes et al, 2019 ). At the same time, bacterial and algal production may be inhibited by high levels of photosynthetically active radiation (Halbach et al, 2022 ; Williamson et al, 2020 ; Yallop et al, 2012 ) and UV (Morgan‐Kiss et al, 2006 ), low nutrient availability (Edwards et al, 2013 ; Hamilton & Havig, 2017 ; Lutz, Anesio, Field, & Benning, 2015 ; Wadham et al, 2016 ), and diurnal freeze–thaw cycles (Cook et al, 2016 ). Dormancy may be a critical ecological strategy used by glacial microorganisms to survive these stresses (Greening et al, 2019 ; Roszak & Colwell, 1987 ; Sussman & Douthit, 1973 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is, in both cases, at the height of the melt season, when liquid water (at ~0.1°C) is widespread on the glacier surface, coinciding with high bacterial and algal activity (Hamilton & Havig, 2017 ; Nicholes et al, 2019 ). At the same time, bacterial and algal production may be inhibited by high levels of photosynthetically active radiation (Halbach et al, 2022 ; Williamson et al, 2020 ; Yallop et al, 2012 ) and UV (Morgan‐Kiss et al, 2006 ), low nutrient availability (Edwards et al, 2013 ; Hamilton & Havig, 2017 ; Lutz, Anesio, Field, & Benning, 2015 ; Wadham et al, 2016 ), and diurnal freeze–thaw cycles (Cook et al, 2016 ). Dormancy may be a critical ecological strategy used by glacial microorganisms to survive these stresses (Greening et al, 2019 ; Roszak & Colwell, 1987 ; Sussman & Douthit, 1973 ).…”
Section: Discussionmentioning
confidence: 99%
“…We focused on light‐absorbing particle‐containing snow and ice samples (following the description from Lutz et al, ( 2014 )). In mid‐July 2019, we collected samples of ice (labelled MIT5) from the bare‐ice surface of Mittivakkat's ablation zone (65.691° N; 37.857° W, altitude 343 masl) (Halbach et al, 2022 ). A few weeks later, in early August 2019, we collected samples of both particle‐containing snow (IS19‐13) and ice (IS19‐14) from the surface of the north‐western edge of Langjökull's ablation zone.…”
Section: Methodsmentioning
confidence: 99%
“…pH measurements were conducted using a standard, portable meter and electrodes (Hanna Instruments, UK) calibrated using new pH 4 and 7 buffers. For microscopy analysis, 13 mL of subsample was removed using a sterile syringe, fixed with 1 mL of 37% formaldehyde (0.2 μm‐filtered) to get a final concentration of c. 2.5% w/v (Halbach et al., 2022) and stored in sterile 15 mL Corning centrifuge tubes. The samples for microscopy were stored in the dark at 4°C and analyzed within 3 months at the University of Sheffield, UK.…”
Section: Methodsmentioning
confidence: 99%
“…At these densities, glacier algal blooms lend a distinctive brownish/purple colouration to the ice surface because of the cells' heavy investment in secondary phenolic pigmentation (Remias et al, 2012 ; Williamson et al, 2020 ); shown to be a key adaptation to life in surface ice that protects against high irradiance (Williamson et al, 2020 ). Given the substantial ice surface darkening and resulting albedo decline associated with the growth of these heavily pigmented microalgal cells (Yallop et al, 2012 ; Di Mauro et al, 2020 ; Halbach et al, 2022 ), glacial algal blooms hold significant potential to exacerbate the melting of glacial ice across the cryosphere: in Greenland, the presence of algae was found to increase melting of high biomass regions by as much as 26% (Cook et al, 2020 ). As liquid water is considered a pre-requisite for glacier algal growth within ice (Williamson et al, 2019 ), the potential exists for establishment of a positive feedback loop between glacier algal growth, ice surface darkening, liquid water generation, and continued bloom proliferation.…”
Section: Introductionmentioning
confidence: 99%